Better survival of right-sided than left-sided stage II colon cancer: a propensity scores matching analysis based on SEER database - Wang, Shuanhu; Xu, Xinxin; Guan, Jiajia; Huo, Rui; Liu, Mulin; Jiang, Congqiao; Wang, Wenbin (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Most studies have found that right-sided colon cancer (RCC) has worse prognosis than left-sided colon cancer (LCC), especially in stage III, but the reported prognosis of stage II colon cancer is variable. This study aimed to evaluate the impact of tumor location on survival outcomes in stage II colon cancer.Materials and Methods: Patients with stage II colon cancer were identified in the Surveillance, Epidemiology, and End Results database from 2004 to 2009. The effect of tumor location on overall survival and cancer-specific survival was analyzed using Cox proportional hazards regression models and propensity score matching.Results: Of 16,519 patients, 69.6% had RCC and30.4% had LCC. In unadjusted analyses, RCC had a 13% increased overall mortality risk (hazards ratio [HR], 1.13; 95% confidence interval [CI], 1.07-1.19; p<0.001) but an18% reduction in cancer-specific mortality risk compared with LCC (HR, 0.82; 95% CI, 0.76-0.89; p<0.001). After propensity scores matching analyses, RCC had a 21% reduced overall mortality risk (HR, 0.79; 95% CI, 0.72-0.87; p<0.001) and a 49% reduction in cancer-specific mortality risk compared with LCC (HR, 0.51; 95% CI, 0.44-0.60; p<0.001).Conclusion: When adjusted for multiple clinicopathological features, stage II RCC showed better prognosis than stage II LCC.